ARTIFICIAL INTELLIGENCE IS REPLACING LANGUAGE TEACHING APPROACHES: ARE TRADITIONAL ESL METHODOLOGIES BECOMING OBSOLETE IN HIGHER EDUCATION? - Elmira Silanteva (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Abstract. The rapid integration of artificial intelligence into higher education has significantly transformed English as a Second Language instruction. AI-powered tools such as intelligent chatbots, automated writing evaluators, adaptive learning systems, speech-recognition applications, and machine translation platforms provide learners with immediate feedback, personalised practice, and continuous access to language support. These developments have raised a controversial question: are traditional ESL methodologies becoming obsolete in university education? This paper critically examines the relationship between artificial intelligence and established approaches such as Grammar-Translation, Communicative language teaching, Task-based language teaching, the Direct method, and the Lexical approach. It argues that AI is not simply replacing traditional methodologies but is changing their functions, implementation, and relevance. Therefore, the future of ESL education lies not in the disappearance of established approaches but in the development of hybrid, human-centred, and technologically supported pedagogical models.
Keywords: Keywords: artificial intelligence, ESL methodology, higher education, traditional teaching approaches, AI-assisted language learning, communicative language teaching, task-based learning, teacher role, personalised learning, hybrid pedagogy